Natural history of infection of the uterine cervix by the human papilloma virus - Wayne D., Lancaster (2015)
The epidemiological association between HPV infection and cervical carcinoma fulfills all of the established epidemiological criteria for causality. The prevalence of HPV infection in young women has been estimated to range from 20-46% in various countries, but recent results from studies in the U.S. suggest that 60% of college-aged women are infected with HPV at some time; the long-term effects of the current high HPV exposure rates and carcinogenesis are unknown. Cervical cancer is regarded as a late consequence of persistent infection of the cervical epithelium by certain HPV types, due to either subtle defects in the host immune response or the ability of the virus to evade the immune system. On the other hand, cervical lesions in the vast majority of women infected with HPV regress suggesting an active cell mediated immune response. These women are also immune to reinfection with the same HPV type. Altogether more than 95% of cervical cancers have been shown to contain HPV sequences. The vast majority of these occur in the cervical transformation zone consisting of squamous metaplastic epithelium. HPV-16 and HPV-18 are the most frequently encountered and occur in about 50-70% of invasive cervical cancer and their precursor lesions.